Estudo do auge e declínio da ovinocultura em estâncias tradicionais de Bagé-RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work has the proposal address the historical importance of sheep in Bagé-RS, more specifically discuss about two distinct periods of ovine livestock. The main focus is to determine, within this agricultural process, what are the elements that converge to the maintenance of the sheep industry in traditional resorts. In this way, through interviews with five traditional producers of the Municipality sought to assess and describe the origins, the facts and the Organization of producers in the decision-making and administration of establishments in times of peak and crisis of the activity. The research made use of theoretical framework for understanding the sheep scene as a whole, you will see the scientific reality of the theme proposed. Between the results found shows how important the maintenance factor creating sheep clinging to tradition passed on from generation to generation. Consequently, the subject presented investigated through a set of precise information a more accurate analysis of one of the most important sectors of agribusiness.
Study of the peak and decline of the sheep in tradicional farms of Bagé-RS
Keywords: Criação de ovinos; Tomada de decisão; Agronegócio; Sheep breeding; Decision-making; Agribusiness; CNPQ::CIENCIAS AGRARIAS